Early growth and death from cardiovascular disease in women. Issue 6918 (11th December 1993) - Osmond, C; Barker, D J; Winter, P D; Fall, C H; Simmonds, S J
Abstract : OBJECTIVE--To determine whether the link suggested between growth in utero and during infancy and death from cardiovascular disease in men is also present in women. DESIGN--Follow up study of women and men whose birth weight and weight at 1 year of age had been recorded. SETTING--Hertfordshire, England. SUBJECTS--5585 women and 10, 141 men born during 1911-30. MAIN OUTCOME MEASURES--Standardised mortality ratios for cardiovascular disease. RESULTS--Among women and men death rates from cardiovascular disease fell progressively between the low and high birth weights groups (chi 2 = 4.3, p = 0.04 for women, chi 2 = 8.5, p < 0.005 for men). Cardiovascular deaths in men but not women were also strongly related to weight at 1 year, falling progressively between the low and high weight groups (chi 2 = 27.5, p < 0.0001). The highest cardiovascular death rates in women were among those with below average birth weight but above average weight at 1 year. In men the highest rates were among those with below average birth weight and below average weight at 1 year. CONCLUSION--Relations between cardiovascular disease and birth weight are similar in men and women. In men cardiovascular disease is also related to weight gain in infancy.